6 - Emerging Reality in Customary Land Tenure: The Case of Kachenga Village in Balaka District, Southern Malawi. - Paul Kishindo (African Sociological Review, 2010)
This paper discusses land tenure changes that have occurred in one village in Balaka district, southern Malawi and the forces that have been at work. The current land tenure system departs in a number significant of ways from what is supposed to be the ideal situation. Among the important changes are the diminishing role of the group village headman as allocator of land rights, increasing importance of family heads as allocaters of land rights and the development of an informal land market.